2021
DOI: 10.1021/acsami.0c22127
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Doped Polysilicon Passivating Contacts for Silicon Solar Cells

Abstract: In this work, we present a simple and efficient solution-doping process for preparing high-quality polycrystalline silicon (poly-Si)-based passivating contacts. Commercial phosphorus or boron-doping solutions are spin-coated on crystalline silicon (c-Si) wafers that feature SiO2/poly-Si layers; the doping process is then activated by thermal annealing at high temperatures in a nitrogen atmosphere. With optimized n- and p-type solution doping and thermal annealing, n- and p-type poly-Si passivating contacts fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Therefore, proper matching of SiO x thickness and dopant concentration is critical to achieving excellent properties in terms of passivation and tunneling current in TOPCon solar cells. [ 27,28 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, proper matching of SiO x thickness and dopant concentration is critical to achieving excellent properties in terms of passivation and tunneling current in TOPCon solar cells. [ 27,28 ]…”
Section: Resultsmentioning
confidence: 99%
“…It has been proved that an oxide of 1.0 nm is sufficient to keep the V OC stable even when the rear‐SRV reaches 1 × 10 7 cm s –1 , and this might be because the oxide suppresses the leakage current. [ 27 ] The front‐SRV is also considered in our study, and the simulation results are shown in Figure 5b. The front‐SRV refers to the carrier recombination rate between a‐Si (p + ) and ITO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] Among them, spin‐on doping is currently attracting interest from the photovoltaic research community due to its convenience and simplicity. [ 26,27 ] The source of dopants for the spin‐on process is a solution of dopant‐containing silicate glass in alcohol. This glass solution can be easily spun onto the Si wafer at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This glass solution can be easily spun onto the Si wafer at room temperature. For higher throughput, such as in an industrial manufacturing line, the solution can potentially be sprayed, [ 25 ] tape cast, [ 28 ] spin‐coated, [ 27 ] or inkjet‐printed. [ 29 ] In addition, this spin‐on doping method brings the benefit of using less toxic precursors compared with conventional gas diffusion or ion implantation processes.…”
Section: Introductionmentioning
confidence: 99%